The Potential of Curcumin as Prevention and Alternative Treatment for Helicobacter Pylori Associated Diseases - Prabandari, Anak Agung Sagung Mirah; Sari, Ni Nyoman Shinta Prasista (Bali Medical and Wellness Journal, 2024)
Introduction: Helicobacter pylori (H. pylori) is a pathogenic bacterium found in half of the world's population, causing gastrointestinal problems ranging from gastritis and peptic ulcers to gastric cancer. Current triple therapy treatment for H. pylori faces issues of resistance, side effects, and high cost, necessitating alternative therapies. Studies suggest that curcumin, a compound found in turmeric, may have antibacterial effects against H. pylori. Method: This literature review evaluated the potential of curcumin against H. pylori infection. Relevant articles were systematically searched in PubMed, Scopus, Web of Science, and Google Scholar databases using combinations of keywords including "curcumin," "turmeric," "Helicobacter pylori," "antibacterial," "anti-inflammatory," "antioxidant," and "bioavailability." Results: Curcumin, a polyphenol compound extracted from turmeric, possesses antibacterial, anti-inflammatory, anti-carcinogenic, and antioxidant properties. Turmeric is a natural, inexpensive, and readily available plant in Indonesia. Curcumin prevents H. pylori-associated diseases by inhibiting bacterial adherence to gastric cells and exhibiting bactericidal effects through disruption of bacterial metabolic enzymes and inhibition of ammonia production. Additionally, curcumin treats H. pylori-induced inflammation by suppressing inflammatory pathways such as NF-κB, AP-1, JNK, and MAPK. Conclusion: Curcumin shows potential as both a preventive and therapeutic agent for H. pylori-associated diseases. Further research should focus on improving curcumin's delivery system to enhance its efficacy in clinical applications.